Event Series: Augustana Campus of the University of Alberta, Camrose, Alberta - Dipple, Geoffrey (The sixteenth century journal, 2017)
The article reports on 2016 and 2017 events held at Augustana Campus of the University of Alberta celebrating the 500th anniversary of the Reformation which included the virtual exhibition entitled "The Reformation in Alberta: A History of the Reformation through Ten Items in the Bruce Peel Special Collections Library," an interfaith panel discussion "Commemorating the Reformation: 500 Years Later," and a scholarly panel of clergy and scholars entitled "Luther: Rebel, Genius, Liberator?"